Antimicrobial activity and effects of sireh (Piper betle L.) extract on controlling bacterial leaf blight disease in rice plant - Abu Asan, Nor Umaira (2022)
Bacterial leaf blight (BLB), caused by Xanthomonas oryzae pv. oryzae (XOO), which is a bacterial disease that leads to substantial losses of rice production. Several control measures have been evaluated by many researchers to reduce the incidence of this disease. However, some of the methods seem to have limited effectiveness. Thus, the application of natural products from Piper betle L. could be an alternative solution, as this plant is well-known in medicinal applications and contains a variety of bioactive compounds. This study was conducted to determine and identify the antibacterial activity and bioactive compounds of P. betle L. extract, respectively, as well as their effectiveness in disease suppression under glasshouse conditions. The antibacterial activity of the P. betle L extract (100, 50, 25, and 12.25 mg/ml) in four different solvents (methanol, ethyl acetate, hexane, and acetone) was evaluated using a disc diffusion assay, Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values. The inhibition zone of methanolic extract appeared to have the highest diameter compared than those of other extracts, which is 32.67 mm at a concentration of 100 mg/ml, followed by 30.33 mm, 22.00 mm, and 20.30 mm for the concentrations of 50 mg/ml, 25 mg/ml, and 12.5 mg/ml, respectively. The MIC and MBC values of the methanolic extract were 0.625 mg/ml suggested that the extract has a bactericidal effect of XOO. The time-kill studies revealed that the 0.625 mg/ml concentration of methanolic extract had a time and concentration-dependent killing effect on XOO. The phytochemical screening was examined for all the extracts and observed the methanolic extract has high content of flavonoids, phenols, and tannins. Gas Chromatography-Mass Spectroscopy (GC-MS) analysis of methanol extract revealed the presence of eugenol acetate [29.53%], 4-allyl-1,2-diacetoxybenzene [29.51%], and 2,3-dimethyl benzoic acid [22.82] as major compounds. The in vivo study of the concentration of 0.625 mg/ml of methanolic P. betle L. extract in glasshouse conditions revealed that the disease reduction percentage was reduced to 52.63% (T2) and 67.02% (T3) as early as day 7 of post-treatment compared with negative control T1. These results demonstrated the treatments with P. betle L. extract were capable of controlling BLB disease, especially with the application of the extract as prevention compared to control of the disease. The methanolic extract of P. betle L. was proven to have an effective inhibitory effect on XOO, and the observation of significant disease suppression in glasshouse conditions indicates that the methanolic extract of P. betle L. may have the potential to be used as an alternative in management strategies for controlling bacterial leaf blight. In the future study, development of a formulation from methanol extract is one of the recommendations to be applied in glasshouse and field trials.